Competição interespecífica entre parasitoides de ceratitis capitata (wiedemann) (diptera: tephritidae) - Dantas, Fernanda Jéssika Carvalho (Universidade Federal Rural do Semi-Árido, 2019)
Fruit flies (Diptera: Tephritidae) have a great economic and quarantine expression, becoming a limiting factor for exports in the northeast region due to the phytosanitary impediment and high percentage of fruit depreciation. The species Ceratitis capitata (Wiedemann) is the only one of the genus present in Brazil and the most used method for its control is still based on synthetic insecticides. However, to minimize the impacts caused by pesticides, alternative controls are used that generate less impacts to the agroecosystem. Among these, the biological control method through the use of parasitoids stands out as a safe and effective alternative for the control of these dipterans, being of great importance to Integrated Pest Management (IPM). Parasitoids such as Diachasmimorpha longicaudata (Ashmead) and Tetrastichus giffardianus (Silvestri) are important natural control agents that have already been used in Classical Biological Control in various parts of the world for the suppression of these tephritids. However, the consortium of two different parasitoids released in an area agricultural may imply impacts on local biodiversity and on the competition among these organisms for oviposition sites. The objective of this study was to evaluate the laboratory behavior of competing parasitoids, either in fruit insertion or in naked larvae, without the direct interaction of natural enemies. For the first competition, 10 day larvae were supplied to D. longicaudata during 5 hours and later provided for T. giffardianus during 24 hours. The larvae exposed to D. longicaudata were collected and inserted in fruits of Goiaba (Psidiumguajava). D. longicaudata excelled in all the competitions carried out with T. giffardianus emergence of 27.04% and 28.95% for nude larvae and guava, respectively. However, it was the increased parasitism rate of T. giffardianus that showed the importance of the experiment with rates of 0.8% and 13.7% in competition, characterizing an increase of 4 larvae parasitized to 72 proving that the behavioral and volatile stimulus of the fruit introduction was effective, suggesting that both species are tolerated. It was found that the emergence of C. capitata fell by 81% without the introduction of natural enemies to 8.38% in the competition of parasitoids on guava fruit. With both species inserted, there was a single parasitism rate equal to 42.65% of parasitoids in the competition with the introduction of guava
Keywords: Mosca-do-mediterrâneo; Inimigo natural; MIP; Controle biológico; Mediterranean fly; Natural enemy; MIP; Biological control; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA